Peningkatan Literasi Artificial Intelligence bagi Siswa SMA sebagai Bekal Menghadapi Era Society 5.0 - Rio Juniyantara Putra; Yahya; Ramli Ahmad; Samsul Al Kifli (Universitas Hamzanwadi, 2026)
The rapid development of Artificial Intelligence (AI) in the Society 5.0 era requires improved technological literacy among high school students as preparation for digital transformation and future competency demands. This Community Service (PkM) activity aims to enhance students’ AI literacy through the introduction of basic AI concepts, ethical use of AI, and its application in supporting the learning process. The activity was conducted at SMA Darussolihin NW Kalijaga involving 23 students through interactive presentations, demonstrations, hands-on practice using ChatGPT, group discussions, and evaluation using pre-test and post-test assessments. The results show that students’ average AI literacy score increased from 64.80 before the activity to 77.87 after the activity, representing an improvement of 20.12%. In addition, students demonstrated improved understanding of basic AI concepts, awareness of ethical AI usage, the ability to utilize AI to support learning, and increased confidence in using technology responsibly. This activity was proven effective in enhancing AI literacy and students’ digital competencies, while also serving as a relevant strategy to strengthen critical thinking skills, encourage responsible technology use, and prepare the younger generation for the challenges and opportunities of the Society 5.0 era.